First‐line pazopanib in intermediate‐ and poor‐risk patients with metastatic renal cell carcinoma: Final results of the FLIPPER trial. Issue 4 (18th August 2020) - Staehler, Michael; Panic, Andrej; Goebell, Peter J.; Merling, Marie; Potthoff, Karin; Herrmann, Edwin; de Geeter, Patrick; Vannier, Corinne; Hogrefe, Cathrin; Marschner, Norbert; Grünwald, Viktor
Abstract: Temsirolimus has long been the only approved first‐line standard of care (SOC) with overall survival (OS) benefit in poor‐risk patients with advanced or metastatic renal cell cancer (mRCC). However, tyrosine kinase inhibitors are also commonly used in clinical practice. Pazopanib is an SOC for first‐line mRCC treatment, but for poor‐risk patients data are scarce. The FLIPPER (First‐Line Pazopanib in Poor‐Risk Patients with Metastatic Renal Cell Carcinoma) study aimed to assess efficacy and safety of first‐line pazopanib in poor‐risk mRCC patients. FLIPPER was a single‐arm, multicenter, Phase IV trial. Key inclusion criteria were treatment‐naive clear cell, inoperable advanced or mRCC, poor‐risk according to MSKCC with slight modification, Karnofsky performance status (KPS) ≥60% and adequate organ function. Oral pazopanib 800 mg was given daily. Primary endpoint was the 6‐month progression‐free survival rate (PFS6). Secondary endpoints included PFS, OS, overall response rate (ORR), duration of response (DOR) and safety. For analysis, descriptive statistics were used. Between 2012 and 2016, 60 patients had been included. Forty‐three patients qualified for safety analyses, 34 for efficacy. Median age was 66 years, 64.7% of patients were poor‐risk, 82.4% had a KPS ≤70%. PFS6 was 35.3% (95% CI, 19.7‐53.5). Median PFS and OS were 4.5 months (95% CI, 3.6‐7.8) and 9.3 months (95% CI, 6.6‐22.2), respectively. ORR was 32.4% (95% CI, 17.4‐50.5), median DOR 9.7 months (95% CI, 1.8‐12.4). The most common treatment‐related grade 3/4 adverse event reported in 4.7% of patients was hypertension. No treatment‐related death occurred. Since pazopanib is active and well tolerated in poor‐risk patients with clear cell mRCC, our results support its use as first‐line treatment in this setting. Abstract : What's new? The tyrosine kinase inhibitor pazopanib was approved for treatment‐naive or cytokine‐pretreated patients with advanced or metastatic renal cell cancer (mRCC) independent of prognosis as determined by the MSKCC risk assessment model. The role of pazopanib in poor‐risk patients remains understudied in trials. The FLIPPER Phase IV trial evaluated the efficacy and safety of pazopanib as first‐line therapy in patients with mRCC with poor‐risk features according to the MSKCC criteria. The results underline that pazopanib is active and well tolerated in poor‐risk mRCC patients with clear‐cell histology, supporting its use as first‐line treatment. During this trial, no new safety signals emerged.